2018
DOI: 10.1038/s41588-018-0156-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic determinants of co-accessible chromatin regions in activated T cells across humans

Abstract: Over 90% of genetic variants associated with complex human traits map to non-coding regions, but little is understood about how they modulate gene regulation in health and disease. One possible mechanism is that genetic variants affect the activity of one or more cis-regulatory elements leading to gene expression variation in specific cell types. To identify such cases, we analyzed ATAC-seq and RNA-seq profiles from stimulated primary CD4 T cells in up to 105 healthy donors. We found that regions of accessible… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
132
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 168 publications
(148 citation statements)
references
References 81 publications
(116 reference statements)
16
132
0
Order By: Relevance
“…Although enhancer RNA QTL might be partly discovered from ChIP-seq for histone 5 marks (e.g., H3K4me1 and H3K27ac), DNase-seq or ATAC-seq, these studies have also been conducted for LCL, blood cells, and other limited types of cells using only hundreds of European or Yoruba individuals (Alasoo et al, 2018;Banovich et al, 2018;Bryois et al, 2018;Degner et al, 2012;Delaneau et al, 2019;Gate et al, 2018;Kumasaka et al, 2019;Pelikan et al, 2018). An alternative approach is the 10 experimental identification of transcribed enhancers (van Arensbergen et al, 2019), but it would still be challenging to conduct such experiments in many types of cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although enhancer RNA QTL might be partly discovered from ChIP-seq for histone 5 marks (e.g., H3K4me1 and H3K27ac), DNase-seq or ATAC-seq, these studies have also been conducted for LCL, blood cells, and other limited types of cells using only hundreds of European or Yoruba individuals (Alasoo et al, 2018;Banovich et al, 2018;Bryois et al, 2018;Degner et al, 2012;Delaneau et al, 2019;Gate et al, 2018;Kumasaka et al, 2019;Pelikan et al, 2018). An alternative approach is the 10 experimental identification of transcribed enhancers (van Arensbergen et al, 2019), but it would still be challenging to conduct such experiments in many types of cells.…”
Section: Discussionmentioning
confidence: 99%
“…Given that the degree to which chromatin is open for transcription factor binding plays an important role in whether any given gene can be expressed in T cells, quantitative assessment of chromatin accessibility is likely to be extremely useful for the study of T‐cell memory. The advent of Assay for Transposase Accessible Chromatin using sequencing has already provided initial insights into human peripheral blood CD4 + T cells . We anticipate that Assay for Transposase Accessible Chromatin using sequencing profiling at bulk and single‐cell levels will provide many new insights into memory CD4 + T cells in humans and experimental animal models.…”
Section: Transcriptional and Metabolic Control Of Memory Cd4+ T‐cell mentioning
confidence: 99%
“…The advent of Assay for Transposase Accessible Chromatin using sequencing 41 has already provided initial insights into human peripheral blood CD4 + T cells. 42,43 We anticipate that Assay for Transposase Accessible Chromatin using sequencing profiling at bulk and single-cell levels will provide many new insights into memory CD4 + T cells in humans and experimental animal models.…”
Section: Transcriptional and Metabolic Control Of Memory Cd4 + T-cellmentioning
confidence: 99%
“…1A; Methods). Activated cells were transfected with 280 sgRNAs targeting 140 regulators that were either highly expressed (top quartile from bulk RNA-seq) or have binding sites that were differentially accessible (from bulk ATAC-seq) in activated CD4 + T cells (18) (Fig. 1B; Table 1; Methods).…”
Section: Crispr Perturbation Screen In Activated Cd4 + T Cells Acrossmentioning
confidence: 99%
“…While the functionalization of CD4 + T cells is predominantly determined by the polarization of naive T cells (T naive ), recent results have suggested a high degree of variation within and plasticity between canonical subtypes (17). Indeed, we (18,19) and others (20)(21)(22) have shown that human circulating CD4 + T cells are composed of a mixture of canonical and non-canonical populations with significant interindividual variability in both the proportion and gene expression of each population (18).…”
mentioning
confidence: 96%